Android app for the hearing and visually impaired - Tan, Feng Yun (2014)
The objective of this project is to design a disabled-friendly and intuitive app that can be run on Android smartphones. This app is intended to enable the hearing and visually impaired communities to lead a fulfilling and independent lifestyle despite the challenges caused by their disabilities. For instance, the speech-to-text functionality allows hearing impaired users to convert audio of any length into text both in real-time and non-real-time. As for the visually impaired, the image-to-audio function enables them to take a snapshot of text containing English words and convert these words into audio both in real-time and non-real-time. In addition, images located within folders on the smartphone can be selected and converted into text. This not only benefits the disabled, it also provides convenience to students who wish to take notes. Last but not least, the translated text and recorded audio files can be backed up to email or uploaded to cloud storage for further use.